The Influence of Organizational Support, Remote Work Policy and Perceived Ease of Use on Employee Digital Engagement of Remote Workers - Mury Andayani; Riesna Apramilda; Enny Diah Astuti; Muhammad Hery Santosa; Tyahya Whisnu Hendratni; Muhammad Abi Berkah Nadi (Journal of Innovative and Creativity, 2025)
This study analyzes the interactions of organizational support, remote working conditions, and perceived usability from the viewpoints of the employees working offsite regarding their engagement with digital tools. The methodology employed in the research was quantitative, and data was gathered by means of a survey with 200 participants. The participants were selected intentionally according to the requirements of having been working remotely for not less than six months and having employed digital technologies in their daily work. The results showed that all three independent variables have a positive and significant effect on employee digital engagement. Organizational support has been shown to increase employee loyalty and emotional attachment, remote work policy strengthens work-life balance and motivation, while perceived ease of use increases digital comfort and participation. Theoretically, this study enriches the literature on digital human resource management, while practically provides guidance for organizations in designing effective, adaptive remote employee management strategies oriented towards sustainable digital engagement.